Effects of Scots Pine Sawdust on Quality, Growth, Photosynthetic Characteristics, and Nutrient Contents of Lavandula officinalis - Nuray Cicek (BioResources)
This study aimed to evaluate the effects of Scots pine (Pinus sylvestris L.) sawdust on the growth, aesthetic quality, photosynthetic pigments, and nutrient uptake of Lavandula officinalis, a widely cultivated medicinal and ornamental plant in Türkiye. Eleven growth media were formulated by mixing peat and perlite with sawdust at concentrations ranging from 5% to 50% (v/v). The results demonstrated that the 25% sawdust treatment significantly enhanced plant height, crown width, fresh weight, and visual appearance. Photosynthetic pigment concentrations (chlorophyll a, b, and carotenoids) were also optimized at this level, while higher sawdust proportions (≥ 40%) led to notable declines. Contrary to expectations, total nitrogen content increased with sawdust levels, possibly due to nitrogen-rich tissues in the sawdust and enhanced microbial mineralization. Calcium content peaked at 25%, whereas micronutrients such as iron, copper, and zinc decreased with higher sawdust ratios. The findings suggest that Scots pine sawdust, when applied at moderate levels, can serve as a sustainable substrate component in lavender cultivation. This is the first study to systematically assess Scots pine sawdust in lavender growing media, contributing to the development of resource-efficient and environmentally friendly horticultural practices.